The Study of Relationship between Social Support and Quality of Life among Elderly People in Kerman - Saideh Garousi; Hossein Safizadeh; Fatemeh Samadian (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background and Objective: As the economic and health status are improving, elderly population are increasing But, it is clear that increased longevity is not per se is sign of development, quality of life is more important. Quality of life of elderly people is influenced by several factors, one of the most important is social support. Previous researches showed that along with increase in social support, elderly people`s quality of life is improved. The aim of this research is finding the relationship between social support and quality of life of the ledelry in the city Kerman, Iran.Subjects and Methods: This survey was performed among 383 elderly men and women living in the city of Kerman. The research tool was a questionnaire with interview; SF36 questionnaire was used for scaling quality of life and a researcher made questionnaire for measuring social support.Results: The most important supporters were, in the first degree, was wife/husband followed by then son and, in third degree, daughter. Mean score of physical quality of life was more than average mental health score. The results showed that emotional support, financial services, advisory and information, and age are all the components of quality of life. Conclusion: According to these findings, increase in the types of social support, especially emotional support, can be of a great help for improvement in the quality of life for seniors. Of course, elderly people need economic and other supportive services in addition to emotional support.